2007
DOI: 10.1038/sj.onc.1210608
|View full text |Cite
|
Sign up to set email alerts
|

The MYST family of histone acetyltransferases and their intimate links to cancer

Abstract: The histone acetyltransferases (HATs) of the MYST family are highly conserved in eukaryotes and carry out a significant proportion of all nuclear acetylation. These enzymes function exclusively in multisubunit protein complexes whose composition is also evolutionarily conserved. MYST HATs are involved in a number of key nuclear processes and play critical roles in genespecific transcription regulation, DNA damage response and repair, as well as DNA replication. This suggests that anomalous activity of these HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
265
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(269 citation statements)
references
References 139 publications
2
265
1
1
Order By: Relevance
“…In addition, biochemical analysis has indicated that ING4 interacts with methylated histone H3 (12)(13)(14) and with the HB01-JADE-hEAF6 histone acetyltransferase complex (11). This latter complex is responsible for most nucleosomal histone H4 acetylation in eukaryotes, and knockdown experiments indicated that Ing4-HB01 association is required for cells to progress properly through the DNA synthesis (S) phase of the cell cycle (15,16).…”
mentioning
confidence: 99%
“…In addition, biochemical analysis has indicated that ING4 interacts with methylated histone H3 (12)(13)(14) and with the HB01-JADE-hEAF6 histone acetyltransferase complex (11). This latter complex is responsible for most nucleosomal histone H4 acetylation in eukaryotes, and knockdown experiments indicated that Ing4-HB01 association is required for cells to progress properly through the DNA synthesis (S) phase of the cell cycle (15,16).…”
mentioning
confidence: 99%
“…Esa1 and TIP60 are orthologous and belong to the MYST family (Doyon and Cote, 2004). Compared to Gcn5/PCAF and p300/CBP, this family is less well known, so it is extensively covered in this edition, Lafon et al (2007) on Esa1, Sas2 and Sas3, the three MYST proteins from yeast; Rea et al (2007) covering mammalian orthologs of Mof (male absent on the first), a key regulator of Drosophila gene dosage compensation; Avvakumov and Coˆte´(2007) outlining the characterization of mammalian MYST proteins; and Yang and Ullah (2007) detailing studies of MOZ and MORF (MOZ-related factor), a pair of paralogs with direct links to leukemia and highly conserved from zebrafish to mammals. In addition to those mentioned above, over 10 other proteins have been reported to possess HAT activity (for reviews, see Sterner and Berger, 2000;Roth et al, 2001;Yang, 2004;Lee and Workman, 2007).…”
Section: Hats Of Different Types and Sizesmentioning
confidence: 99%
“…Based on the nature of their catalytic domains, HATs can be grouped into two distinct families: the GCN5-related N-acetyltransferase (GNAT) family, which includes GCN5 and p300/CBP-associating factor (8), and the Moz-Ybf2/Sas3-Sas2-Tip60 (MYST) family, which is characterized by a highly conserved MYST domain composed of an acetyl-CoA binding motif and a zinc finger (9,10). Some MYST family members also have additional structural features such as chromodomains (MOF, Esa1, and Tip60), plant homeodomain-linked zinc fingers (Moz and MORF), and other domains that bind specifically to modified histones or participate in other protein-protein interactions (10).…”
mentioning
confidence: 99%